1998
DOI: 10.1037/0022-0663.90.2.312
|View full text |Cite
|
Sign up to set email alerts
|

A split-attention effect in multimedia learning: Evidence for dual processing systems in working memory.

Abstract: Students viewed a computer-generated animation depicting the process of lightning formation (Experiment 1) or the operation of a car's braking system (Experiment 2). In each experiment, students received either concurrent narration describing the major steps (Group AN) or concurrent on-screen text involving the same words and presentation timing (Group AT). Across both experiments, students in Group AN outperformed students in Group AT in recalling the steps in the process on a retention test, in finding named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
628
4
39

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 994 publications
(698 citation statements)
references
References 18 publications
27
628
4
39
Order By: Relevance
“…The results suggest that dual-presentation modalities may increase working memory resources by activating both auditory and visual working memory rather than just one (Mousavi, Low, & Sweller, 1995). In a similar fashion, Mayer and Moreno (1998) found that the superiority of simultaneous narrations and animations over simultaneous text and animations is consistent with a dual-processing model of working memory with separate channels for visual and auditory processing. Students were presented with a computer-generated animation depicting the process of lightning formation (Experiment 1)-or the operation of a car's braking system (Experiment 2).…”
Section: Modality Principlesupporting
confidence: 69%
See 1 more Smart Citation
“…The results suggest that dual-presentation modalities may increase working memory resources by activating both auditory and visual working memory rather than just one (Mousavi, Low, & Sweller, 1995). In a similar fashion, Mayer and Moreno (1998) found that the superiority of simultaneous narrations and animations over simultaneous text and animations is consistent with a dual-processing model of working memory with separate channels for visual and auditory processing. Students were presented with a computer-generated animation depicting the process of lightning formation (Experiment 1)-or the operation of a car's braking system (Experiment 2).…”
Section: Modality Principlesupporting
confidence: 69%
“…In Mayer and Moreno's (1998) study, students who learned with concurrent narration and animations outperformed those who learned with concurrent on-screen text and animations. These results might be interpreted as being due to two different effects: a spatial-contiguity effect and a modality effect.…”
Section: Distinguishing Modality and Contiguity Principlesmentioning
confidence: 95%
“…In short, the eyes initially receive input from two sources (as indicated by the arrow from words to eyes and from pictures to eyes). This hypothesis is derived from a cognitive theory of multimedia learning in which visually presented material is processed (at least initially) in a limited-capacity visual channel, whereas auditorily presented material is processed (at least initially) in a limitedcapacity auditory channel (Mayer, 1997(Mayer, , 1999a(Mayer, , 1999cMayer & Moreno, 1998). The split-attention hypothesis predicts that adding on-screen text to a narrated animation will result in poorer performance on retention and transfer tests.…”
Section: Methodsmentioning
confidence: 99%
“…The multimedia explanation uses animation to depict the steps in lightning formation along with corresponding narration to describe them. Our research has documented that well designed multimedia explanations formatted like the one in Figure 1 can be highly effective in promoting students' understanding, as indicated by their ability to generate acceptable answers to open-ended transfer questions (Mayer, 1997(Mayer, , 1999a(Mayer, , 1999cMayer & Moreno, 1998;Moreno & Mayer, 1999).…”
mentioning
confidence: 99%
“…text, discourse) surpass analogue modalities (e.g. images, graphics, diagrams) at explaining abstract concepts; while analogue modalities are better at expressing what things exactly look like [7]; at the perception level: use an additional auditory modality if using only a visual modality can cause overload in the visual perception channel [16]; and at the structural level: the combination of an icon and a map is able to describe both an object and its location [3].…”
Section: Related Workmentioning
confidence: 99%